Global marketplace strategy and choice of interaction after termination of international joint venture1. (25th April 2019) - Parameswar, Nakul; Dhir, Sanjay
Abstract: Foreign partner's global marketplace strategy significantly influences the choice of interaction after international joint venture (IJV) termination as supplier–buyer, complement, or competitor between terminated IJV partners. The domestic partner in IJV enables foreign firms to pursue its global marketplace strategy—transnational, multidomestic, global, or international. On IJV termination, foreign partner's perceived value creation from IJV shall be rendered void and is required to either look for a new domestic firm to collaborate or form an interaction after IJV termination with IJV's domestic partner. This study examines the role of foreign firm's global marketplace strategy on the choice of interaction after IJV termination as supplier–buyer, complement, or competitor using data on terminated two partner IJV headquartered in India.